Women in Sports and Exercise: From Health to Sports Performance - Clemente, Filipe; Silva, Ana Filipa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The current book presents the articles included in the Special Issue "Women in Sports and Exercise: From Health to Sports Performance". Readers will find in this book evidence about the relationships between physical qualities in sports and how women's performance can be optimized using dedicated training intervention. Moreover, information about the impact of the menstrual cycle on athletic performance will be revealed. Attention to physical activity patterns in women will be also disclosed.